1985
DOI: 10.1007/bf00391889
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of mononuclear cell infiltrations in colorectal adenocarcinoma

Abstract: Mononuclear cell (MNC) populations in tissue specimens from 11 colorectal adenocarcinomas and 1 mucinous adenocarcinoma were analyzed, applying different monoclonal antibodies (MoAB). Tumor epithelium could be characterized by MoAB VEP9, predominantly binding to mucus secreted by the tumor cells. In approximately 30%-50%, the tumor epithelium also reacted in a patchy pattern with the MoABs OKT10 and OKIa, which define in the peripheral blood activated and HLA-DR expressing cells. T-lymphocytes, as defined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…As shown in this study and by others (Svennevig et al, 1982;Svennevig et al, 1984;Allen and Hogg, 1985;Koch et al, 1985;Umpleby et al, 1985), the infiltration of mononuclear cells, as found in almost all tumours, was generally restricted to the stromal areas with fairly few cells infiltrating between tumour cells. This indicates chemotactic activity causing inflammatory cells to leave the blood vessels, but the migration of inflammatory cells close to tumour cells is inhibited.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…As shown in this study and by others (Svennevig et al, 1982;Svennevig et al, 1984;Allen and Hogg, 1985;Koch et al, 1985;Umpleby et al, 1985), the infiltration of mononuclear cells, as found in almost all tumours, was generally restricted to the stromal areas with fairly few cells infiltrating between tumour cells. This indicates chemotactic activity causing inflammatory cells to leave the blood vessels, but the migration of inflammatory cells close to tumour cells is inhibited.…”
Section: Discussionsupporting
confidence: 53%
“…The presence of CD4+ and CD8+ tumour-infiltrating lymphocytes in colorectal cancer has varied in different studies (Csiba et al, 1984;Lennard et al, 1984;Allen and Hogg, 1985;Koch et al, 1985;Umpleby et al, 1985;Ebert et al, 1989). The conflicting results might to some extent be explained by the complex situation in these tumours, in which cytotoxic and immunosuppressor activities are present simultaneously (for further discussion see below).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations